How can doctoral supervision be improved? Views from doctoral students in two faculties of education at South African universities - Akala, B. U.; Akala, B. M. (South African Journal of Higher Education, 2023)
This study aims to address the void left by earlier researchers by establishing how full-time doctoral students’ views can be employed to improve doctoral studies. By employing habitus, field, social and cultural capital, and agency as a theoretical framework for this article, open-ended questions in a qualitative study were designed and executed purposively among sampled doctoral candidates at two faculties of education in South African universities. This approach was hinged on the thought that what PhD candidates were going through was vital when thinking of improving PhD supervision. Out of this study, PhD students point to some of their experiences as the starting point for possible supervision improvement. The study findings reveal that if academic leadership at the faculty level is actively involved in this process at the strategy formulation level, the experiences of students can change for the better. This can be done through the introduction and establishment of seminars, small and large group engagements, and the widening of social capital. Widening of social capital will ensure that both PhD supervisors and PhD students share productive supervision experiences while buttressing multidirectional relationships between supervisors, students and their peers aimed at improving completion rates and the doctoral journey.